Clinical Course of Small Subepithelial Tumors of the Small Bowel Detected on CT - Seohyun Kim; Seung Joon Choi; Su Joa Ahn; So Hyun Park; Young Sup Shim; Jeong Ho Kim (대한영상의학회지, 2022)
Purpose This study aimed to evaluate the natural growth of subepithelial tumors of the small bowel detected on CT. Materials and Methods Consecutive patients who were suspected of having subepithelial tumors of the small bowel between January 2005 and December 2020 were reviewed. Eligible patients with suspected small (< 30 mm) subepithelial tumors on at least two CT evaluations were included in the analysis. The patients’ data on demographic characteristics, tumoral characteristics, and tumoral size changes during the follow-up were collected. Results This study included 64 patients with suspected small subepithelial tumors (n = 64) of the small bowel. After a median follow-up of 15.8 months, the diameter and volume growth rates were 0.02 mm/month and 1.5 mm3/month, respectively. A significant correlation was observed between the initial size and the growth rate of the small bowel subepithelial tumors. The group of large-sized tumors (initial diameter ≥ 10 mm) tended to show lobulated contours, heterogeneous enhancement, and necrotic changes more frequently than the group of small-sized tumors (initial diameter < 10 mm). Conclusion Small bowel subepithelial tumors measuring less than 10 mm grew more slowly than those measuring 10–30 mm.